The moral dimensions of health: pilot study - Becker, Maria; Ananth, Swetha; Kiemes, Carina (Discourse Lab, 2023)
Pilot study by Maria Becker (Heidelberg), Svetha Ananth (Heidelberg) and Carina Kiemes (Darmstadt) Morality plays an important role in everyday life and influences almost all areas of our society, e.g., politics, culture, religion, or education. When people are debating about … Weiterlesen →
Gesehen am 09.10.2023